Comparison of slide coagglutination test and the conventional method in the identification of n. gonorrhoeae in freshly-voided urine and cervical specimens of symptomatic and asymptomatic females. - Syson, Maria A. (1983)
Gram's stain of cervical smear is unreliable for the diagnosis of gonorrhea among infected females. 10 (30.3 ) were not detected with the Gram's smear from a total of 33 infected individuals with positive culture. Culture method is the most dependable way for detecting these female carriers, but the confirmatory carbohydrate utilization test can prolong the diagnosis up to 1 week. Phadebact Gonococcus Test is an excellent substitute of the conventional method. This Coagglutination test (COA) makes confirmatory diagnosis possible within 24 hours. It was proven in this paper that Phadebact GC Test is highly specific and is as sensitive as the conventional method. With Phadebact GC Test, presumptive identification with oxidase test and Gram's stain can even be omitted. Collecting urine is much easier than collecting cervical specimen and infection with contaminated speculum can be avoided. Uncertrifuged urine was found to be as sensitive as the cervical specimen though the colonies isolated from the uncertrifuged urine were fewer in number because of the dilution of the gonococci with the urine. Conversely, the centrifuged urine gave a lower sensitivity than the cervical specimen. This may be because the N. gonorrhoeae were inhibited or killed by the other microorganisms in the urine when the urine was left standing before it could be processed and the urine sediment could be cultured.